ИССЛЕДОВАНИЕ ВЛИЯНИЕ КОМПОНЕНТОВ НА СВОЙСТВА КЛЕЕВЫХ КОМПОЗИЦИЙ ДЛЯ ГОФРИРОВАННЫХ КАРТОНОВ - Шарипов, Музафар; Тиллаева, Дилдора (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Based on the analysis of various modern research methods, it is explained how the components of an adhesive composition based on oxidized starch affect the properties of the polymer composition and the reasons for this.